Role of Macrophage Colony Stimulating Factor in Drug Resistance - Chockalingam S, S (My University, 2013)
Cancer cells acquiring resistance to chemotherapeutic drugs remain the most serious obstacle to the development of an efficient anti-cancer therapy. Overexpression of ABC transporter genes is associated with active expulsion of chemotherapeutic drugs from cancer cells. Many tumor cells overexpress Macrophage Colony Stimulating Factor (MCSF), which acts as the chemoattractant, infiltrating the tumor with circulating monocytes and promoting metastasis of tumor. Moreover, tumors with augmented expression of MCSF show poor prognosis with treatment. This thesis aims to explore the properties of Macrophage Colony Stimulating Factor when combined with the conventional anti-cancer drug 5- fluorouracil (5-FU) on a human glioblastoma cell line, U87MG. Introductory section of this thesis describes the current strategies employed in anti-cancer therapies and the genes responsible for drug resistance. An extensive review on molecular signaling mechanisms of MCSF is described in Review of literature. This section also provides deeper insight into the role played by MCSF in supporting tumor growth. In Materials and Methods, information about the chemicals and reagents used along with the methodologies employed in the work are discussed in detail. The fourth section of the thesis, Results and Discussion started with cloning of MCSF from mammalian cells followed by generation of a stable cell line of U87MG constitutively expressing MCSF, named as U87-MCSF cells. Upon 5-FU treatment, the proliferation of U87-MCSF was significantly affected as determined by cell cycle analysis and cyclin expression studies. The retardation in the cell proliferation did not lead to apoptosis; rather resulted in a change in morphology.
Ghosh, Siddhartha S.
Keywords: BIOSCIENCES AND BIOENGINEERING